Introdução à Teoria dos Jogos para o Ensino Médio - Santos, Cleverton Souza (2016)
This work has an educational proposal for the content of Logic, Matrices and Probability in high school, but the real goal is the intention of the insertion in the curriculum, of itself relevant, Game Theory. A historical introduction motivating the study followed the presentation ctional situations, distant from reality, as well as some close to everyday problems, treated lightly, sometimes with some irreverence, bring the Logic elements, Matrices and Probability to the fore. It also presents the essences elements of Game Theory and some solutions proposed by it. At work consists also a demonstration of the Minimax Theorem accessible to every high school student and nally has to display a more sophisticated mathematical reasons all content.